2018
DOI: 10.1111/jfpe.12870
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of bruteridin and melitidin from clarified bergamot juice by membrane operations

Abstract: Four commercial spiral‐wound membranes with nominal molecular weight cut‐off (NMWCO) from 150–300 to 3,500 Da were tested in order to evaluate their performance in the recovery of brutieridin and melitidin from clarified bergamot juice. Filtration experiments in batch concentration mode were performed on a laboratory filtration membrane equipment in selected operating conditions up to a weight reduction factor (WRF) of 5. The performance of selected membranes was evaluated in terms of permeate flux and rejecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…A full rejection towards glucose and fructose was also detected in the treatment of bergamot juice with a spiral-wound PA membrane having a MWCO of 150–300 Da [ 48 ]. Similarly, Arboleda Mejia et al [ 37 ] reported very high rejections towards glucose and fructose for some lab-made cellulose acetate NF membranes used in the treatment of red grape pomace extract.…”
Section: Resultsmentioning
confidence: 99%
“…A full rejection towards glucose and fructose was also detected in the treatment of bergamot juice with a spiral-wound PA membrane having a MWCO of 150–300 Da [ 48 ]. Similarly, Arboleda Mejia et al [ 37 ] reported very high rejections towards glucose and fructose for some lab-made cellulose acetate NF membranes used in the treatment of red grape pomace extract.…”
Section: Resultsmentioning
confidence: 99%